Pengaruh kesadaran pajak dan sanksi pajak terhadap kepatuhan membayar Pajak Bumi Dan Bangunan di Desa Pinabetengan Utara - Christopher Harry Ayub Tandaju; Inggriani Elim; I Gede Suwetja (Riset Akuntansi dan Portofolio Investasi, 2026)
The decline in Land and Building Tax (PBB) revenue realization in North Pinabetengan Village in 2025, which reached only 62% of the target, indicates a taxpayer compliance problem. This study aims to analyze the partial and simultaneous effects of tax awareness and tax sanctions on taxpayer compliance in paying PBB in North Pinabetengan Village, grounded in the Theory of Planned Behavior (TPB). The study employed a quantitative causal-associative approach. The population consisted of 438 taxpayers, with a sample of 82 respondents determined using the Slovin formula through proportionate stratified random sampling. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression with SPSS version 30. The results show that, partially, tax awareness has a positive and significant effect on taxpayer compliance (t = 4.966; Sig. < 0.01), as do tax sanctions (t = 6.237; Sig. < 0.01). Simultaneously, both variables have a significant effect (F = 90.890; Sig. < 0.01). The Adjusted R² of 0.689 indicates that tax awareness and tax sanctions explain 68.9% of the variation in taxpayer compliance, while the remaining 31.1% is explained by other factors outside the model. These findings confirm that the combination of internal factors (awareness) and external factors (sanctions) plays an important role in shaping PBB taxpayer compliance behavior in rural areas.